Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69019
|View full text |Cite
|
Sign up to set email alerts
|

The Efficient Computation of Transient Flow in Turbine Blade Rows Using Transformation Methods

Abstract: Computational predictions of the transient flow in turbine blade rows are considered. Adjacent blade rows typically contain unequal numbers of blades and vanes, requiring a computation over multiple passages per row to permit application of simple periodic boundary conditions. For typical geometries, use of conventional solution methods requires computation over all or a significant portion of the wheel to ensure a time accurate solution. The computational load is significantly reduced by method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Hence, the simulations demonstrated that LES could now be used in house, for this type of flow. Connell et al (2012) apply the SAS hybrid RANS-LES approach. The key aspect of this work is that it proposes time-inclining (see Chap.…”
Section: Non-flat Plate Lpt Simulationsmentioning
confidence: 99%
“…Hence, the simulations demonstrated that LES could now be used in house, for this type of flow. Connell et al (2012) apply the SAS hybrid RANS-LES approach. The key aspect of this work is that it proposes time-inclining (see Chap.…”
Section: Non-flat Plate Lpt Simulationsmentioning
confidence: 99%
“…For the time-integration methods, they consist of the time-shifted methods and the scaling methods. The former is mainly the Fourier transformation (FT) method, which is based on the time shift and phase shift [10], and it is improved by introducing the Fourier series decomposition at the rotor/stator and periodic interfaces [11,12]. This makes the significant data compression and efficiency improvement with two blade passages modeled per row, but it usually needs more calculation periods to reach convergence [13].…”
Section: Introductionmentioning
confidence: 99%
“…The TT method was validated on several test cases [12,[18][19][20]. However, the discussion of this method in the open literature was more concerned about the total performance parameters (mass flow, efficiency, and total pressure ratio) and time-averaged variables.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic boundary conditions are implemented using a simple phase shift of the complex amplitudes, which are solved for the frequencies of the perturbations coming from adjacent computational domains with different rotational speeds. Detailed explanation of this technique is available in the literature [25][26][27][28][29].…”
Section: Interface Modeling Techniquesmentioning
confidence: 99%
“…A method called a Fourier transformation is used in this technique [25][26][27]. Two research groups modeled the Francis turbine using this technique and presented the results during the workshop [6,16].…”
Section: Interface Modeling Techniquesmentioning
confidence: 99%